Wireless LAN interface card design - Wang, Bing (2008)
A wireless local area network (LAN) interface card is used to transmit and receive data over the air by using radio frequency technology in wireless LAN systems. Although the advancement of digital communication and semiconductor technology has led to the development of the wireless LAN interface card technique, the first generation cards were designed to operate with workstation. Having high power consumption and large size, the first generation cards were unsuitable for battery operated portable computers. The low data rate of these cards made them unsuitable to be used in multimedia technology. In addition, due to not having technology standards, the first generation wireless LAN interface cards could not allow for interoperability for mobile workforce. The purpose of the study is to overcome these drawbacks, and develop a wireless LAN interface card to have high data rate, long distance coverage and low power consumption so as to be incorporated into lap-top, notebook, and pen-pad computers.